Gas-chromatographic determination of deltamethrin in crops - Navickiene, Sandro [UNESP]; Kato, Marta H. [UNESP]; Polese, Luciana [UNESP]; Minelli, Elizabeth V. [UNESP]; Ribeiro, Maria L. [UNESP] (Springer Nature, 1998)
A rapid and economical method is described for the determination of deltamethrin in wheat, rice, peanuts and corn. It is based on simultaneous extraction and clean-up on a column packed with alumina and silica gel using n-hexane-ethyl ether (8:2, v/v), followed by a derivatization step and gas-chromatographic analysis. Recoveries from fortified cereal and peanut samples were determined at four concentration levels and ranged from 73 to 109%. The detection limits were 0.01 to 0.03 mg/ kg. This method simplifies the traditional procedures in terms of sample size, solvent consumption and analysis time. © Springer-Verlag 1998.